Flame-Retardant and Thermal Degradation Mechanism of Caged Phosphate Charring Agent with Melamine Pyrophosphate for Polypropylene - Xuejun Lai; Jiedong Qiu; Hongqiang Li; Xingrong Zeng; Shuang Tang; Ye Chen; Zhen Chen (International Journal of Polymer Science)
An efficient caged phosphate charring agent named PEPA was synthesized and combined with melamine pyrophosphate (MPP) to flame-retard polypropylene (PP). The effects of MPP/PEPA on the flame retardancy and thermal degradation of PP were investigated by limiting oxygen index (LOI), vertical burning test (UL-94), cone calorimetric test (CCT), and thermogravimetric analysis (TGA). It was found that PEPA showed an outstanding synergistic effect with MPP in flame retardant PP. When the content of PEPA was 13.3 wt% and MPP was 6.7 wt%, the LOI value of the flame retardant PP was 33.0% and the UL-94 test was classed as a V-0 rating. Meanwhile, the peak heat release rate (PHRR), average heat release rate (AV-HRR), and average mass loss rate (AV-MLR) of the mixture were significantly reduced. The flame-retardant and thermal degradation mechanism of MPP/PEPA was investigated by TGA, Fourier transform infrared spectroscopy (FTIR), TG-FTIR, and scanning electron microscopy-energy dispersive X-ray spectrometry (SEM-EDXS). It revealed that MPP/PEPA could generate the triazine oligomer and phosphorus-containing compound radicals which changed the thermal degradation behavior of PP. Meanwhile, a compact and thermostable intumescent char was formed and covered on the matrix surface to prevent PP from degrading and burning.